Beroahan Local Tradition of Commmunity in Kotabaru, Melawi West Kalimantan - M. Farid Migustio (Khatulistiwa, 2018)
Communities always have local wisdom for their interests and survival. Like wise with the community in Kotabaru, Tanah Pinoh District, Melawi Regency, West Kalimantan. Based on data obtained through interviews and observations at Kotabaru, the community inherited many local traditions; one of them is prayer. Beroah is a tradition of Kotabaru people who are chosen, carried out by people who want to do it, and usually carried out by capable communities. In the past until now prayers have always been carried out by Muslim communities to pray or send prayers to people who passed away. The aim is to pray for people who passed away. Prayers are usually carried out when the day of one's death and can also be carried out after the second, third, seventh, one hundredth and even one thousandth day.